2001
DOI: 10.1023/a:1009489518468
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The data points to measurable differences in the uterine PI and RI between the tubal infertility and male infertility in the natural cycles. These differences were abolished after ovarian stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…After stratifying the studies according to the previously identified age bands, a mean ovarian PI of 1.49 [1.38–1.60], 2.69 [2.03–3.35], 1.57 [0.46–2.67], 0.80 [0.65–0.95], and 2.96 [2.66–3.26] was found in the 1st (< 20 years; n = 1 study) [ 57 b], 2nd (≥ 20 and < 25 years; n = 5 studies) [ 24 , 36 , 76 , 77 , 82 ], 3rd (≥ 25 and < 30 years; n = 3 studies) [ 3 , 37 , 101 ], 4th (≥ 30 and < 35 years; n = 4 studies) [ 33 , 46 , 70 , 93 ], and 5th groups (≥ 35 years; n = 1 study) [ 83 ], respectively, with a statistically significant difference between the five groups ( Q = 187.57, p < 0.0001) (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…After stratifying the studies according to the previously identified age bands, a mean ovarian PI of 1.49 [1.38–1.60], 2.69 [2.03–3.35], 1.57 [0.46–2.67], 0.80 [0.65–0.95], and 2.96 [2.66–3.26] was found in the 1st (< 20 years; n = 1 study) [ 57 b], 2nd (≥ 20 and < 25 years; n = 5 studies) [ 24 , 36 , 76 , 77 , 82 ], 3rd (≥ 25 and < 30 years; n = 3 studies) [ 3 , 37 , 101 ], 4th (≥ 30 and < 35 years; n = 4 studies) [ 33 , 46 , 70 , 93 ], and 5th groups (≥ 35 years; n = 1 study) [ 83 ], respectively, with a statistically significant difference between the five groups ( Q = 187.57, p < 0.0001) (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%